1
$\begingroup$

This thread is Q&A.

Given Hilbert spaces $\mathcal{H}_0$ and $\mathcal{H}$.

Consider Hamiltonians: $$H_\#:\mathcal{D}(H_\#)\to\mathcal{H}_\#:\quad H_\#=H_\#^*$$

Denote their evolutions: $$U_\#(t)^*=U_\#(-t)=U_\#(t)^{-1}$$

For an operator: $$J:\mathcal{H}_0\to\mathcal{H}:\quad\|J\|<\infty$$

Assume the limit: $$\Omega\varphi:=\lim_{t\to\infty}U(t)^*JU_0(t)\varphi\quad(\varphi\in\mathcal{H})$$

Then one obtains: $$\big(H\restriction_\overline{\mathcal{R}\Omega}\big)=\big(H\restriction_\overline{\mathcal{R}\Omega}\big)^*\cong\big(H_0\restriction_\overline{\mathcal{R}\Omega^*}\big)=\big(H_0\restriction_\overline{\mathcal{R}\Omega^*}\big)^*$$

How can I prove this?

$\endgroup$
0
$\begingroup$

Note that one has: $$(\mathcal{N}\Omega)^\perp=\overline{\mathcal{R}\Omega^*}=\overline{\mathcal{R}|\Omega|}$$

Denote embeddings: $$J^0_\overline{\mathcal{R}\Omega^*}\in\mathcal{B}\big(\overline{\mathcal{R}\Omega^*},\mathcal{H}_0\big):\quad\big(J^0_\overline{\mathcal{R}\Omega^*}\big)^*\big(J^0_\overline{\mathcal{R}\Omega^*}\big)=1_\overline{\mathcal{R}\Omega^*}$$ $$J_\overline{\mathcal{R}\Omega}\in\mathcal{B}\big(\overline{\mathcal{R}\Omega},\mathcal{H}\big):\quad\big(J_\overline{\mathcal{R}\Omega}\big)^*\big(J_\overline{\mathcal{R}\Omega}\big)=1_\overline{\mathcal{R}\Omega}$$

Restrict Hamiltonians: $$H^0_\overline{\mathcal{R}\Omega^*}:=\big(J^0_\overline{\mathcal{R}\Omega^*}\big)^*H_0\big(J^0_\overline{\mathcal{R}\Omega^*}\big)\quad H_\overline{\mathcal{R}\Omega}=\big(J_\overline{\mathcal{R}\Omega}\big)^*H\big(J_\overline{\mathcal{R}\Omega}\big)$$

By reducibility one has:* $$\big(H^0_\overline{\mathcal{R}\Omega^*}\big)=\big(H^0_\overline{\mathcal{R}\Omega^*}\big)^*\quad\big(H_\overline{\mathcal{R}\Omega}\big)=\big(H_\overline{\mathcal{R}\Omega}\big)^*$$

Polar decomposition: $$\Omega=J_\Omega|\Omega|:\quad(J_\Omega)^*(J_\Omega)=1_\overline{\mathcal{R}\Omega^*}\quad(J_\Omega)(J_\Omega)^*=1_\overline{\mathcal{R}\Omega}$$

Denote unitary map: $$U_\Omega:\overline{\mathcal{R}\Omega^*}\to\overline{\mathcal{R}\Omega}:\quad U_\Omega\varphi:=J_\Omega\varphi$$

By unitarity one has:** $$\big(J_\overline{\mathcal{R}\Omega}\big)^*U(t)\big(J_\overline{\mathcal{R}\Omega}\big)\big(U_\Omega\big)=\big(U_\Omega\big)\big(J^0_\overline{\mathcal{R}\Omega^*}\big)^*U_0(t)\big(J^0_\overline{\mathcal{R}\Omega^*}\big)$$

By Stone's theorem: $$\big(H_\overline{\mathcal{R}\Omega}\big)=(U_\Omega)\big(H^0_\overline{\mathcal{R}\Omega^*}\big)(U_\Omega)^*$$

Concluding equivalence.

*See the thread: Reducibility

**See the thread: Unitarity

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.